Company Bankruptcy Prediction Analysis: The Altman Z"-Score Method - Yustisia, Natali; Khairuna, Lainun (Business, Management & Accounting Journal (BISMA), 2025)
The purpose of this study  is to analyze the effect of the ratio of Working Capital to Total Asset, Retained Earnings to Total Asset, Earnings Before Interest and Tax to Total Asset, and Market Value of Equity to Book Value of Liability on bankruptcy predictions.  The sample used was ten companies obtained by purposive sampling method from State-Owned Enterprises in the infrastructure service sector listed on the Indonesia Stock Exchange during the 2021-2023 period.  This study is a quantitative research using the logistic regression estimation method processed using the Statistical Package for Social Sciences 30 software.  The results of the study using the Wald Test found that Working Capital to Total Asset had a significant negative effect on bankruptcy prediction, while Retained Earnings to Total Asset, Earnings Before Interest and Tax to Total Asset, and Market Value of Equity to Book Value of Liability had no significant influence on bankruptcy prediction.  Inaddition, the results of the Omnibus Test of Model Coefficients mentioned that all independent variables simultaneously have a significant effect on bankruptcy prediction.